Electro‐Induced Mechanical and Thermal Responses of Carbon Nanotube Fibers. (12th February 2014) - Meng, Fancheng; Zhang, Xiaohua; Li, Ru; Zhao, Jingna; Xuan, Xiaohui; Wang, Xinhao; Zou, Jingyun; Li, Qingwen
<x xml:space="preserve">Abstract</x> The electromechanical and electrothermal responses of carbon nanotube fibers provide new ways to use energy conversion, including the modulation of assembly structures by alternative densification and relaxation. The most efficient way to strengthen the tensile strength up to 2.32—2.50 GPa is shown as well as a microscale, nanotube‐based Chinese calligraphy brush. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>